Women's Under-Representation in the Engineering and Computing Professions: Fresh Perspectives on a Complex Problem - Catherine Hill (Frontiers Research Topics, 2018)
Understanding the many complexities that define gender inequality has been described by researchers as a grand challenge. Novel insights, innovation, a broader community to conduct research and to ascertain effective interventions are essential in the challenge to create organizations that are gender equal. As such, this Research Topic in Frontiers in Psychology addresses the under-representation of women in engineering and computing as a complex, but solvable problem. This Research Topic seeks to inform the global community about advances in understanding the under-representation of women in engineering and computing with a focus on what enables change. Further, this Topic will promote fresh perspectives, innovative methodologies, and mixed method approaches important to accelerating the pace of change.